Strengthening local government budgeting and accountability - Schaeffer, Michael (Policy research working paper, 2008)
"In many developing and middle-income countries, decentralization reforms are promoting changes in governance structures that are reshaping the relationship between local governments and citizens. The success of these decentralization reforms depends on the existence of sound public financial systems both at the central and local levels. This paper focuses on the role of budgeting as a critical tool in reform efforts, highlighting problems that might impede successful local government budget development and implementation. The attainment of effective local government accountability and transparency is not an end itself, but rather it represents the means to support better decision-making on national and local budgeting. Community based schemes for enhancing local government accountability need to combine legal, political, and administrative mechanisms with proactive community involvement. Of particular importance are the legal and budgetary instruments that require input from local community members on certain local government decisions and instruments that increase accessibility for the press or the general public at large to information on government activities. "--World Bank web site